2004
DOI: 10.1016/j.physletb.2004.04.043
|View full text |Cite|
|
Sign up to set email alerts
|

One-loop weak corrections to γ/Z hadro-production at finite transverse momentum

Abstract: We illustrate the effects of one-loop weak corrections onto the production of neutral gauge bosons of the Standard Model at RHIC-Spin, Tevatron and LHC, in presence of quark/gluon radiation from the initial state. We find such effects to be rather large, up to O(10 − 20%) in typical observables at all such colliders, where the cross section is measurable, thus advocating their inclusion in precision analyses.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…[11,12]. Since there are no restrictions on the number of jets or charged leptons in isolated photon events, tree level O(α s α 2 ) V γj (V = W ± , Z) production should be included in the calculation.…”
Section: B Isolated Photon Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11,12]. Since there are no restrictions on the number of jets or charged leptons in isolated photon events, tree level O(α s α 2 ) V γj (V = W ± , Z) production should be included in the calculation.…”
Section: B Isolated Photon Productionmentioning
confidence: 99%
“…The blue curve shows R γj (p T (γ)) if only the O(α) virtual weak corrections [11,12] are taken into account. It has been obtained by incorporating the leading O(α) virtual weak corrections of Ref.…”
Section: B Isolated Photon Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that at high energies, the electroweak corrections from virtual weak boson exchange increase strongly. This fact motivated the calculation of the complete one-loop electroweak corrections to large-p T photon production in hadronic collisions [31,32]. Indeed it was found that at the LHC, where photon transverse momenta in the range of 2 TeV are within reach, these corrections amount to up to -17% [32].…”
Section: Prompt Photons In Hadronic Collisionsmentioning
confidence: 97%
“…Numerical results for the one-loop corrections to the latter two processes can be also found in Ref. [8]. In the following we briefly report on the calculations of the gauge boson (V ) production in association with a jet ( j) in the process p p (−) → V j, presented in Refs.…”
mentioning
confidence: 99%